A solid-phase dot assay using silica/gold nanoshells - Zharov Vladimir; Khlebtsov Boris; Dykman Lev; Bogatyrev Vladimir; Khlebtsov Nikolai (Nanoscale Research Letters, 2006)
Abstract We report on the first application of silica-gold nanoshells to a solid-phase dot immunoassay. The assay principle is based on staining of a drop (1 µl) analyte on a nitrocellulose membrane strip by using silica/gold nanoshells conjugated with biospecific probing molecules. Experimental example is human IgG (hIgG, target molecules) and protein A (probing molecules). For usual 15-nm colloidal gold conjugates, the minimal detectable amount of hIgG is about 4 ng. By contrast, for nanoshell conjugates (silica core diameter of 70 nm and gold outer diameter of 100 nm) we have found significant increase in detection sensitivity and the minimal detectable amount of hIgG is about 0.5 ng. This finding is explained by the difference in the monolayer particle extinction.